Citizenship, Compassion, the Arts: People Living with Mental Illness Need a Caring Community. (June 2018) - Potash, Jordan S.; Ho, Rainbow T. H.; Ho, Andy H. Y.
Furthering social inclusion for marginalised members of society demands advocacy efforts focussed on holistic citizenship. Harnessing compassion, the arts can activate four component elements: narratives, actual stories and voices of members of a society; encounters, opportunities for dialogue among members of a society; reflection, values clarification and self-awareness and community, spaces that allow for creative engagement. This theoretical framework is demonstrated in an 18-month campaign designed to promote social inclusion by decreasing stigma and increasing public awareness of people living with mental illness in Hong Kong. The programme utilised an art exhibition created by people living with mental illness, guided relational viewing art-making workshops for the general public, and collaborative art-making opportunities. Integrating compassion and the arts into the citizenship framework provided participants with opportunities to engage with one another, clarify misconceptions and arrive at meaningful social policy programmatic initiatives.